Analisis Kapasitas Struktur Atas Jembatan Mahakam IV (Tipe Arch Bridge) Kalimantan Timur - Yudi Pranoto; Yunus Nanna Padudung; Sectalonir Sectalonir (Jurnal Aplikasi Teknik Sipil, 2021)
The construction of Mahakam IV bridge is motivated by the problem of vehicle traffic congestion that occurs in the Mahakam I Bridge area. This study aims to determine the forces that occur, and also find out the safety profile used. The research method was started by modeling the Mahakam IV Bridge in the Midas Civil program, and than calculated loadingstandar use SNI 1725-2016 and then calculated according to the RSNI T-03-2005 standard. After that, an analysis is carried out on the Midas Civil program to get the results in the form of axial force, shear force and moment. The results of the Midas civil program are the largest axial force value of 1583394 kg, the shear force of 8547.18 kg, and the moment of 14070.61 kg.m. From the results of this analysis, it can be concluded that the girders are elongated, transverse girders, and the mainframe is safe.